Education on healthy living culture to increase children's awareness from an early age - Trimaya Cahya Mulat; Muh Ihsan Kamaruddin; Nordianiwati Nordianiwati (Jurnal Pengabdian Masyarakat Edukasi Indonesia, 2025)
A healthy lifestyle from an early age is an important foundation to support children's growth and development and prevent various diseases in the future. This Community Service Program aims to provide education about healthy living culture to children, to increase their awareness of the importance of maintaining physical and mental health. This activity is carried out through interactive and fun approaches, such as educational games, picture stories, and simulations of healthy living practices, including handwashing habits, a balanced diet, physical activity, and the importance of maintaining a clean environment. The method used involves the active participation of children and mentoring from parents or teachers to ensure the sustainability of the practices taught. The evaluation was carried out by measuring the improvement of children's understanding through pre-test and post-test as well as direct observation of changes in their behavior. The results of this program show a significant increase in children's knowledge and awareness of a healthy living culture. This program is expected to be a model that can be replicated in various communities to create a healthier and more productive generation.